Cortical Activation Patterns to Speech Differ Between Two Age Groups of Older Adults. - Aronsona, Yarden; Zaltz, Yael (Journal of Speech, Language & Hearing Research, 2025)
Purpose: Speech perception is a complex process integrating sensory, cognitive, and linguistic functions, particularly in challenging conditions. Although age-related declines in these areas are well documented, research on speechin-noise (SIN) perception has largely overlooked the very elderly1 (80-91 years old), despite their rapidly growing demographic. This study investigated agerelated differences in cortical activation patterns in response to speech in quiet and noisy environments within a cohort of older adults. Method: The study included 33 less elderly (65-77 years old) and 21 very elderly (80-91 years old) adults, all living independently, generally healthy, and with ageappropriate hearing and cognitive levels. Participants completed two 90- to 120- min sessions involving functional Near-Infrared Spectroscopy to measure cortical activation during speech tasks under varied conditions, SIN recognition tests, and assessments of auditory, cognitive, and linguistic abilities. Results: Significant age-related differences in the pattern of cortical activation were observed. The very elderly exhibited heightened activation in the left temporopolar region, associated with semantic processing, while the less elderly showed greater activation in the left dorsolateral prefrontal cortex, linked to executive functions. Behavioral assessments revealed poorer SIN recognition and significant declines in auditory resolution, attention, and inhibition for the very elderly. Conclusions: This study provides novel insights into the neural adaptations accompanying advanced aging. The findings suggest a progressive shift from reliance on executive control mechanisms in less elderly adults to semantic processing strategies in the very elderly, driven by cumulative declines in sensory and cognitive functions. These results underscore the need for age-specific auditory rehabilitation approaches that leverage residual cognitive and linguistic capacities, particularly for the very elderly.